DIVERSITY PHENETICS OF TYPES SEAGRASS IN VILLAGE POKA BEACH MALUKU BASED ON MORPHOMETRICS - Siahaya, Chalvin Salmon; Tuapattinaya, Prelly Marsell Jolanda; Melay, Stevin (RUMPHIUS, 2022)
This research aims to determine the phenetic diversity of seagrass species in the coastal waters of Poka Village based on morphometrics. This research is a type of descriptive research, in which morphometric measurements are carried out to determine the phenetic diversity of seagrass species. Meanwhile, for kinship relationships between seagrasses. Software is used past 4.0. The results of this research were that four types of seagrass were found, namely Thalasssia hemprichii, Enhalus acoroides, Halophila pinifolia and Halophila ovalis. This indicates that the Poka Village beach has a high phenetic diversity of seagrass species with varying morphometrics for each character and type, which is influenced by the type of substrate and environmental parameters. Seagrasses that are closely related, namely, Thalasssia hemprichii and Enhalus acoroides are in one monophyletic group (ingroup) and are very closely related. Likewise with Halodule pinifolia and Halophila ovalis.